Resolving trabecular metaphyseal bone profiles downstream of the growth plate adds value to bone histomorphometry in mouse models - Salmon, P. L.; Monzem, S.; Javaheri, B.; Oste, L.; Kerckhofs, G.; Pitsillides, A. A. (Frontiers in Endocrinology, 2023)
Introduction Histomorphometry of rodent metaphyseal trabecular bone, by histology or microCT, is generally restricted to the mature secondary spongiosa, excluding the primary spongiosa nearest the growth plate by imposing an ‘offset’. This analyses the bulk static properties of a defined segment of secondary spongiosa, usually regardless of proximity to the growth plate. Here we assess the value of trabecular morphometry that is spatially resolved according to the distance ‘downstream’ of—and thus time since formation at—the growth plate. Pursuant to this, we also investigate the validity of including mixed primary–secondary spongiosal trabecular bone, extending the analysed volume ‘upstream’ by reducing the offset. Both the addition of spatiotemporal resolution and the extension of the analysed volume have potential to enhance the sensitivity of detection of trabecular changes and to resolve changes occurring at different times and locations. Method Two experimental mouse studies of trabecular bone are used as examples of different factors influencing metaphyseal trabecular bone: (1) ovariectomy (OVX) and pharmacological prevention of osteopenia and (2) limb disuse induced by sciatic neurectomy (SN). In a third study into offset rescaling, we also examine the relationship between age, tibia length, and primary spongiosal thickness. Results Bone changes induced by either OVX or SN that were early or weak and marginal were more pronounced in the mixed primary–secondary upstream spongiosal region than in the downstream secondary spongiosa. A spatially resolved evaluation of the entire trabecular region found that significant differences between experimental and control bones remained undiminished either right up to or to within 100 μm from the growth plate. Intriguingly, our data revealed a remarkably linear downstream profile for fractal dimension in trabecular bone, arguing for an underlying homogeneity of the (re)modelling process throughout the entire metaphysis and against strict anatomical categorization into primary and secondary spongiosal regions. Finally, we find that a correlation between tibia length and primary spongiosal depth is well conserved except in very early and late life. Conclusions These data indicate that the spatially resolved analysis of metaphyseal trabecular bone at different distances from the growth plate and/or times since formation adds a valuable dimension to histomorphometric analysis. They also question any rationale for rejecting primary spongiosal bone, in principle, from metaphyseal trabecular morphometry.